Designing and developing online facilities reservation and notification system for Multimedia College Telekom Malaysia / Maizatul Farah Diba Mohd Nordin - Mohd Nordin, Maizatul Farah Diba (Faculty of Computer and Mathematical Sciences, 2007)
Facilities Reservation System (FRS) is the online reservation system for Multimedia College. This system was designed to convert the manual booking system to a standard reservation system. FRS is been set up to give services for internal and external user an easy way of making reservation of room in this College. This project aims to create an online or web based reservation system where users can make their reservation online without wasting their time calling the coordinator for room booking. FRS is a system designed to allowed user to make reservation or cancel it online. A user interface for a Facilities Reservation System (FRS) was developed using Macromedia Dreamweaver and the interfaces of the system were designed using Adobe Photoshop, Macromedia Flash MX is being used as a programming language platform for designing and developing this portal. MySQL is the database programs that been used in this system Apart from that, the system also was developed with SMS notification services by using the Ozeki Server online. As a conclusion, this prototype achieved the objectives and succeeds in doing the task for the college. The systems also had already been deploy and used by the administrator of Multimedia College.